EFFECT OF IMMERSION TIME TO MECHANICAL STRENGTH OF POLYVINYL ALCOHOL– HYDROXY APATITE COMPOSITE AS BIODEGRADABLE BONE PLATE : PENGARUH WAKTU PERENDAMAN TERHADAP KEKUATAN MEKANIS KOMPOSIT POLIVINIL ALKOHOL–HIDROKSI APATIT SEBAGAI FIKSASI FRAKTUR TULANG - Widowati Siswomihardjo; Marsetyawan Heparis Nur Ekanda Soesatyo; Alva Edy Tontowi; Mochammad Taha Ma’ruf (Dentika: Dental Journal, 2013)
Polymer based material such as Poly-L-Lactic-Acid (PLLA) have been used for titanium substitution. However, the last research indicates that it was not an ideal material as bone fracture fixation device. It is a challenge to develop other materials as biodegradable bone plate for titanium substitution, such as polyvinyl alcohol (PVA). In this study, polyvinyl alcohol has composited with Hydroxy apatite (HA) and reinforced with catgut fiber. The aim of this study was to know the effect of immersion time to mechanical strength of PVA– HA composite with catgut reinforced as biodegradable bone plate after biodegradation test for 30 and 60 days. Specimens were prepared for tensile and bending strength tests, immersed in phosphate buffered saline (PBS) solution with pH 7.4 at 370C. Specimens were weighed before and after biodegradation test, tensile and bending test were done after removed for 30 and 60 days. The result showed that PVAHA composite reinforced with catgut fiber has stable mechanical strength after 30 and 60 days biodegradation process. The mechanical strength decreased in 30 and 60 days in all intervention groups, but it still has adequate mechanical strength as biodegradable bone plate. In conclusion, PVA-HA composite reinforced with catgut fiber can be developed as biodegradable bone plate replace titanium and other commercial bone plate.